Aspek Kelisanan dalam Naskah “Hikayat Raja-Raja Siam” - Khofifah Tri Lestari (Madah: Jurnal Bahasa dan Sastra, 2022)
The purpose of this study was to elaborate the oral aspects contained in Hikayat Raja-Raja Siam based on  Walter J. Ong’s orality theory . The object of this research is the text of Hikayat Raja-Raja Siam from collections of Leiden University.  This study used descriptive qualitative method . The researcher read  carefully the literary work before analyzingit based on  Walter J. Ong’s  orality theory . The results of this study show that there are four aspects of orality in Hikayat Raja-Raja Siam. They are conservative or traditional,  exaggerative or elaborate, additive, and participatory forms.  Moreover, this study shows that Hikayat Raja-Raja Siam also tries to reveal the uniqueness of traditionality in Malay literature. The existence of a written tradition does not necessarily make the oral tradition disappear, instead the author then uses the residue of the oral culture as an aesthetic in his work.